Special education teachers’ views on their agency in teacher collaboration - Paloniemi Annukka; Björn Piia M.; Kärnä Eija (United Kingdom, 2022)
Special education teachers’ (SETs) views on their agency in teacher collaboration were analysed using Cultural-Historical Activity Theory (CHAT). Finnish SETs (N = 238) answered open-ended survey questions concerning successful and unsuccessful collaboration with the classroom teachers in a tiered support framework. The findings revealed that the perceived agency of the special education teachers is both limited by and directed towards the classroom teachers’ understanding of the shared responsibility concerning support provision for students. Finally, the findings highlight the relevance of the cultural-historical activity theory by suggesting that the features of successful collaboration, in tandem with relevant constructs of the theory, constitute a mutual understanding of the goal of collaboration (shared object), structures (community) and guidance (norms) towards relevant use of instruments and fair division of responsibilities (division of labour). Implications for inclusive special education suggest that reciprocal reflection on the teaching practices requires shared everyday work between the SETs and the classroom teachers.